Preserved Perspective Taking in Free Indirect Discourse in Autism Spectrum Disorder - Zimmermann, Juliane T.; Meuser, Sara; Hinterwimmer, Stefan; Vogeley, Kai (Frontiers in Psychology, 2021)
Perspective taking has been proposed to be impaired in persons with autism spectrum disorder (ASD), especially when implicit processing is required. In narrative texts, language perception and interpretation is fundamentally guided by taking the perspective of a narrator. We studied perspective taking in the linguistic domain of so-called Free Indirect Discourse (FID), during which certain text segments have to be interpreted as the thoughts or utterances of a protagonist without explicitly being marked as thought or speech representations of that protagonist (as in direct or indirect discourse). Crucially, the correct interpretation of text segments as FID depends on the ability to detect which of the protagonists “stands out” against the others and is therefore identifiable as implicit thinker or speaker. This so-called “prominence” status of a protagonist is based on linguistic properties (e.g. grammatical function, referential expression), in other words, the perspective is “hidden” and has to be inferred from the text material. In order to test whether this implicit perspective taking ability that is required for the interpretation of FID is preserved in persons with ASD, we presented short texts with three sentences to adults with and without ASD. In the last sentence, the perspective was switched either to the more or the less prominent of two protagonists. Participants were asked to rate the texts regarding their naturalness. Both diagnostic groups rated sentences with FID anchored to the less prominent protagonist as less natural than sentences with FID anchored to the more prominent protagonist. Our results that the high-level perspective taking ability in written language that is required for the interpretation of FID is well preserved in persons with ASD supports the conclusion that language skills are highly elaborated in ASD so that even the challenging attribution of utterances to protagonists is possible if they are only implicitly given. We discuss the implications in the context of claims of impaired perspective taking in ASD as well as with regard to the underlying processing of FID.